Development of Learning Videos On The Content Of The Human Respiratory System Materials in Science Subjects on Students Grade Five in Elementary School - Wulandari, I Gusti Ayu Yusri; Surya Abadi, Ida Bagus Gede (International Journal of Elementary Education, 2021)
The availability of learning media in grade five are very lass varied, especially three-dimensional learning media which have characteristics that are suitable for elementary school students. This causes students to find it difficult to understand the subject matter and students get bored easily in classroom. This study was aimed to find out the validity of Pop-Up Book teaching and learning media toward the Pancasila valuase lesson in daily life on students grade five in elementary school. This study applied Dick & Carry model consisted of eight steps. The subjects in this study is Pop-Up Book. The try-out design in this study consisted of expert review for the teaching and learning content, expert review for the teaching and learning design and expert review for teaching and learning media, personal tryout and small group tryout. The data in this development study were collected by administrating formative test from the expert review and students. Data collection techniques in this study were observation, interviews and questioner. Then, the data were analyzed by using qualitative descriptive technique and quantitative descriptive technique. The validity of mean score of the teaching and learning content shown 93.18% with excellent qualification, teaching and learning design shown 89.28% with good qualification, the teaching and learning media shown 91.66% with excellent qualification. Whereas personal tryout shown 95.83% and small group tryout shown 94.90%. Based on the analysis data above, this study could be concluded that the development of Pop-Up Book Model using Dick & Carry was valid.